The trans-silencing capacity of invertedly repeated transgenes depends on their epigenetic state in tobacco - Fojtová, Miloslava; Bleys, Annick; Bedrichová, Jana; Van Houdt, Helena; Krízová, Katerina; Depicker, Anna; Kovarík, Ales (Nucleic acids research, 2006)
We studied the in trans-silencing capacities of a transgene locus that carried the neomycin phosphotransferase II reporter gene linked to the 35S promoter in an inverted repeat (IR). This transgene locus was originally posttranscriptionally silenced but switched to a transcriptionally silenced epiallele after in vitro tissue culture. Here, we show that both epialleles were strongly methylated in the coding region and IR center. However, by genomic sequencing, we found that the 1.0 kb region around the transcription start site was heavily methylated in symmetrical and non-symmetrical contexts in transcriptionally but not in posttranscriptionally silenced epilallele. Also, the posttranscriptionally silenced epiallele could trans-silence and trans-methylate homologous transgene loci irrespective of their genomic organization. We demonstrate that this in trans-silencing was accompanied by the production of small RNA molecules. On the other hand, the transcriptionally silenced variant could neither trans-silence nor trans-methylate homologous sequences, even after being in the same genetic background for generations and meiotic cycles. Interestingly, 5-aza-2-deoxy-cytidine-induced hypomethylation could partially restore signaling from the transcriptionally silenced epiallele. These results are consistent with the hypothesis that non-transcribed highly methylated IRs are poor silencers of homologous loci at non-allelic positions even across two generations and that transcription of the inverted sequences is essential for their trans-silencing potential.
Keywords: DNA Methylation; transgeny; RNA, Untranslated; Kanamycin Kinase; metylace DNA; reportérové geny; umlčování genů; epigeneze genetická; Repetitive Sequences, Nucleic Acid; kanamycinkinasa; nekódující RNA; Plants, Genetically Modified; Nicotiana; repetitivní sekvence nukleových kyselin; geneticky modifikované rostliny; Gene Silencing; Alleles; Transgenes; Genes, Reporter; alely; tabák; Epigenesis, Genetic